High-load copper monatomic nano-enzyme as well as preparation method and application thereof

By preparing high-loaded copper single-atom nanoenzymes, combined with GOx and HA modification, the problem of insufficient H2O2 content in the tumor microenvironment is solved, efficient catalytic ROS generation and tumor targeted treatment are achieved, and the effect and safety of tumor treatment are improved.

CN119837835AInactive Publication Date: 2025-04-18SOUTHWEST PETROLEUM UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510337264.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-21
Publication Date
2025-04-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

There are many disadvantages of existing tumor treatment technologies, such as traditional therapies are prone to residual tiny lesions or trigger metastasis, chemotherapy/radiotherapy is accompanied by severe toxic side effects and drug resistance, targeted treatment is limited by tumor heterogeneity and drug resistance mutations, low response rate of immunotherapy and may induce immune-related adverse reactions, and insufficient H2O2 content in the tumor microenvironment is difficult to support continuous catalytic reactions.

Method used

High-loaded copper single-atom nanoenzyme is used to react SiO2 particles with components such as resorcinol, formaldehyde, and copper ions through the preparation method to form Cu-SAC@GOx@HA nanoenzyme. Its mesoporous hollow structure and copper single-atom support are used to combine glucose oxidase (GOx) and hyaluronic acid (HA) modifications to enhance catalytic activity and targeting in the tumor microenvironment.

Benefits of technology

It has achieved efficient catalyzing of H2O2 production·OH in the restricted tumor microenvironment, cutting off tumor energy supply, enhancing oxidative damage to tumor cells, and improving treatment effect. At the same time, the circulation time and targeting of drugs are improved through HA modification, and reducing toxic side effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119837835A_ABST
    Figure CN119837835A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of biological materials, and discloses a high-load copper monatomic nano-enzyme, a preparation method and application, and the preparation method comprises the following steps: step 1, adding SiO2 particles into a mixed solution of resorcinol and formaldehyde, fully reacting and mixing, and adding a solution containing copper ions to obtain a precursor material SiO2 / Cu-HCN; 2, sufficiently mixing the SiO2 / Cu-HCN with a nitrogen source, and carbonizing to obtain a carbon precursor material; residual SiO2 is removed, and Cu-SAC is obtained; step 3, loading GOx on the Cu-SAC to obtain Cu-SAC coated GOx; step 4, carrying out HA modification on the Cu-SAC-coated GOx, so as to obtain the required high-load copper monatomic nano enzyme HA-coated Cu-SAC-coated GOx; the preparation method comprises the following steps: preparing copper monatomic hollow mesoporous carbon spheres from a copper-doped precursor product, loading GOx, and carrying out HA modification to obtain nano-enzyme; the method is used for chemotherapy and chemical kinetics therapy, and a new construction thought is provided for design and biomedical application of a novel nano-catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biomaterials, and in particular to a high-load copper single-atom nanozyme, a preparation method and an application thereof. Background Art

[0002] At present, there are many drawbacks in tumor treatment technology, such as traditional therapies are prone to residual micro-lesions or cause metastasis, chemotherapy / radiotherapy is accompanied by serious toxic side effects and drug resistance and affects surrounding tissues. Targeted therapy is limited by tumor heterogeneity and drug resistance mutations, immunotherapy has a low response rate and may induce immune-related adverse reactions.

[0003] Inspired by enzyme reaction kinetics, nanozymes with redox activity have unique physicochemical properties and stability that are higher than natural enzymes, and are low-cost. By combining the catalytic properties of enzymes with the physicochemical properties of nanomaterials, nanozymes can use the higher-than-normal levels of H2O2, hypoxia and other characteristics in the TME unique to tumor cells to develop PDT, SDT, CDT and other ROS-generating treatments. ROS can participate in cell signaling, immune regulation, etc.; but when excessive, it can cause oxidative stress and damage biological macromolecules (such as DNA, proteins, lipids), which can be used for tumor treatment. However, the H2O2 content in the TME is difficult to support the continued catalytic reaction. A new treatment method is urgently needed. Summary of the invention

[0004] In view of the problems existing in the prior art, the present invention provides a high-load copper single-atom nanozyme, a preparation method and an application.

[0005] The technical solution adopted by the present invention is: a method for preparing a high-load copper single-atom nanozyme, comprising the following steps: Step 1: Add SiO2 particles to a mixed solution of resorcinol and formaldehyde, fully react and mix, then add a solution containing copper ions, fully react, wash, centrifuge, and dry to obtain a precursor material SiO2 / Cu-HCN; Step 2: Fully mix the SiO2 / Cu-HCN obtained in step 1 with a nitrogen source, and obtain a carbon precursor material after carbonization; remove the remaining SiO2 to obtain Cu-SAC; Step 3: Disperse the Cu-SAC obtained in step 2 in a solution containing glucose oxidase GOx, fully react, wash, centrifuge, and freeze-dry to obtain Cu-SAC@GOx; Step 4: Place the Cu-SAC@GOx obtained in step 3 in a hyaluronic acid HA solution, allow to react fully, and then centrifuge and freeze-dry to obtain the desired high-load copper single-atom nanozyme HA@Cu-SAC@GOx.

[0006] Further, the preparation method of SiO2 in step 1 is as follows: Tetrapropoxysilane and ethyl orthosilicate are dispersed in an alkaline solvent at a molar ratio of 1:1-2 and reacted under stirring conditions.

[0007] Furthermore, in step 1, the molar ratio of tetrapropoxysilane to resorcinol is 1:1.25-2, the concentration of copper ions in the copper ion-containing solution is 0.1-1 mM, and the reaction is carried out under stirring conditions.

[0008] Furthermore, in step 2, the nitrogen source is urea, and the mass ratio of SiO2 / Cu-HCN to urea is 1:3-4.

[0009] Furthermore, in step 2, the carbonization temperature is 900°C, the heating rate is 4°C / min, and the heating time is 2h.

[0010] Furthermore, in step 2, HF solution is used to remove the remaining SiO2, and the concentration of the HF solution is 10 wt.%.

[0011] Furthermore, in step 3, the mass ratio of Cu-SAC to GOx is 1:2, and the reaction is carried out under stirring.

[0012] Furthermore, in step 4, the mass ratio of Cu-SAC@GOx to HA is 1:2, and the reaction is carried out under stirring conditions.

[0013] A high-loaded copper single-atom nanozyme, wherein the nanozyme is a mesoporous hollow structure on which copper single atoms are loaded.

[0014] An application of a high-load copper single-atom nanozyme, and the application of the nanozyme in the preparation of tumor treatment drugs.

[0015] The beneficial effects of the present invention are: (1) The nanozyme obtained by the present invention has a hollow mesoporous structure, and copper is dispersed on the carbon carrier in the form of single atoms, which can respond to TME to catalyze H2O2 to produce ·OH, and maximize its effect in the restricted TME; (2) The nanozyme obtained by the present invention is loaded with GOx, which can catalyze the oxidation process of glucose to provide H2O2 and gluconic acid, while reducing the generation of adenosine triphosphate ATP, cutting off the energy supply required by tumor tissues. CDT and decomposition therapy cascade response, so that the oxidative damage of tumor cells can be achieved to achieve the therapeutic purpose; (3) The surface of the nanozyme obtained by the present invention is coated with HA, which can increase its circulation in the blood and can enter the cell after recognizing the tumor cell surface receptor CD44, thereby reducing the premature release of the drug in the blood circulation and increasing the amount of drug entering the cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1It is a schematic diagram of the process of the present invention.

[0017] Figure 2 Schematic diagram of the microstructure of Cu-SAC obtained in step 2 of Example 1 of the present invention, a is a SEM image, b is a TEM image, and c is an AC-HAADF-STEM image.

[0018] Figure 3 Schematic diagram of the test results of Cu-SAC obtained in step 2 of Example 1 of the present invention, a is the specific surface area and pore size distribution, b is the X-ray diffraction diagram, and c is the Raman spectrum of the substances obtained in comparative example 1 and step 2.

[0019] Figure 4 Schematic diagram of the test results of Cu-SAC obtained in step 2 of Example 1 of the present invention, a is the normalized XANES spectrum of Cu K edge with copper foil, Cu2O and CuO, b is the FT-EXAFS spectrum with copper foil, Cu2O and CuO, c is the EXAFS fitting result in R space, and d is the EXAFS fitting result in K space.

[0020] Figure 5 These are the test results of the materials obtained in each step of Example 1 of the present invention. a is a comparison chart of the ultraviolet absorption spectra of the reaction of H2O2 and GOx with TMB of the materials obtained in step 2, step 3 and Example 1, and b is the electron spin resonance spectrum of the material obtained in Example 1 in the presence or absence of H2O2.

[0021] Figure 6 The biocompatibility results of the substances obtained in each step of Example 1 of the present invention are shown in Figure 1, a is the EC cell result, b is the MCF cell result, and c is the 4T1 cell result.

[0022] Figure 7 This is a fluorescence image of ROS generation in the substance 4T1 cells obtained in each step of Example 1 of the present invention.

[0023] Figure 8 This is the fluorescence image of ·OH in the substance 4T1 cells obtained in each step of Example 1 of the present invention.

[0024] Fig. 9 The CLSM images of the mitochondrial membrane potential of 4T1 cells obtained in each step of Example 1 of the present invention are shown.

[0025] Fig.10 These are the test results of material cytotoxicity obtained in each step of Example 1 of the present invention, a is a fluorescent staining image using AM / PI probe to detect material toxicity, and b is a flow cytometer to measure the cell apoptosis rate caused by incubation of 4T1 cells with different materials. DETAILED DESCRIPTION

[0026] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.

[0027] like Figure 1 As shown, a method for preparing a high-load copper single-atom nanozyme comprises the following steps: Step 1: Add SiO2 particles to a mixed solution of resorcinol and formaldehyde, and after sufficient reaction and mixing, add a solution containing copper ions, and after sufficient reaction, wash, centrifuge, and dry to obtain a precursor material SiO2 / Cu-HCN.

[0028] First prepare SiO2: Ammonia water, ethanol and RO water are mixed in a volume ratio of 5 to 10:80:20, and tetrapropoxysilane and tetraethyl orthosilicate are added dropwise under stirring; wherein the molar ratio of tetrapropoxysilane to tetraethyl orthosilicate is 1:1 to 2, the rotation speed during the addition is 400 to 600 r / min, the rotation speed after the addition is 600 to 800 r / min, and the reaction time is 2 h; a solution containing SiO2 particles is obtained.

[0029] Since the ethoxy group (—OCH2CH3) in ethyl orthosilicate has a small steric hindrance and a fast hydrolysis rate, it is easy to generate silicic acid (Si(OH)4) monomers under acidic or alkaline conditions, promoting rapid nucleation. In contrast, the propoxy group (—OCH2CH2CH3) has a larger steric hindrance and a slower hydrolysis rate, which reduces the speed of releasing silicic acid monomers and slows down the nucleation rate. Slow hydrolysis prolongs the particle growth time, and the particles tend to grow in aggregates, and the larger the particle size. Therefore, the smaller the tetrapropoxysilane and ethyl orthosilicate, the smaller the SiO2 particle size.

[0030] The speed should not be too high during the dropwise addition process, as it will cause the liquid to fill the entire cavity and affect the dropwise addition process. If the reaction time is too long, it may promote polycondensation and increase the particle size.

[0031] Add resorcinol solution and formaldehyde solution to the solution containing SiO2 particles under stirring; (resorcinol can be dissolved by ultrasonication and then added to the solution containing SiO2 particles together with formaldehyde solution) The molar ratio of tetrapropoxysilane to resorcinol is 1:1.25-2, and the ratio of resorcinol to formaldehyde is adjusted according to the actual situation, and generally formaldehyde is excessive. At room temperature, the speed is 400-500 r / min, and after the addition is completed, the speed is 900-1000 r / min, and the reaction time is 10 h.

[0032] The solution containing copper ions was added to the solution obtained after the reaction under stirring conditions. After the copper ion solution was added, the concentration of copper ions in the solution was 0.1~1 mM, the reaction temperature was room temperature, the speed was adjusted to 1000 r / min, and the reaction time was 12 h. After sufficient reaction, the reaction solution was washed twice with ethanol and RO water to remove ammonia and ethanol in the reaction solution, and the precursor material SiO2 / Cu-HCN was obtained by centrifugation at 9000 r / min and drying at 60 °C for 6 h.

[0033] The reaction needs to be carried out at room temperature. In order to avoid the system temperature rising due to long-term stirring, the outside of the reaction device is cooled by water flow during the reaction. Excess formaldehyde is mainly used to regulate the reaction process, optimize product performance, and ensure the formation of an ideal three-dimensional cross-linked network structure. The specific reason is that excess formaldehyde can promote the hydroxymethylation reaction to proceed fully, so more hydroxymethylphenol intermediates are generated. On the one hand, further condensation and cross-linking between hydroxymethyl groups can generate a three-dimensional network structure and a mesoporous structure. On the other hand, formaldehyde itself contains a large number of ether bonds, which can bind a large number of copper ions on its surface in combination with hydroxymethyl groups. During high-speed stirring, the copper ions can be dispersed more evenly and the active sites can be increased.

[0034] Step 2: Grind the SiO2 / Cu-HCN obtained in step 1 thoroughly and mix it with urea at a mass ratio of 1:3-4; place them in a quartz crucible and transfer them to a tube furnace, and heat and carbonize them in an argon atmosphere; the heating temperature is 900 °C, the heating rate is 4 °C / min, and the heating time is 2 h.

[0035] The obtained powder was dispersed in a 10 wt.% HF solution and stirred at 200 r / min for 12 h to remove the remaining SiO2; it was washed with 95% ethanol and RO water until neutral, then centrifuged at 9000 r / min for 15 min, and finally dried at 60 °C for 6 h to obtain Cu-SAC.

[0036] During the high-temperature carbonization process, functional groups such as hydroxyl (—OH) and carboxyl (—COOH) in phenolic resin will decompose into gases such as CO2 and H2O, which will escape, reduce the oxygen content of the material, form oxygen vacancies, and evaporate the metal clusters. Urea will decompose at high temperatures to produce nitrogen-containing gases such as ammonia (NH3) and isocyanic acid (HNCO). These gases will react with the carbon skeleton of phenolic resin on the surface of SiO2 / Cu-HCN to form CN bonds (such as pyridinic nitrogen, pyrrolic nitrogen, and graphitic nitrogen), thereby significantly increasing the nitrogen content in the material. The presence of pyridinic nitrogen and pyrrolic nitrogen can provide the sites required for copper atoms to anchor. NH3 gas can also be used as a pore former to increase the specific surface area and enhance the exposure of nitrogen-doped sites.

[0037] Excessive urea may leave undecomposed nitrogen precursors, while too low a ratio will result in insufficient nitrogen doping. Increasing the urea mass ratio can achieve high nitrogen and low oxygen conditions. High temperature can promote deoxidation but may cause nitrogen loss. The temperature needs to be controlled to achieve a balance between the gains and losses. Too fast a heating rate will result in incomplete heating, while too slow a heating rate will increase the carbonization time and evaporate excess copper.

[0038] Since the three-dimensional cross-linked network structure formed during carbonization enables HF to etch SiO2 so that the resulting Cu-SAC eventually has a hollow mesoporous structure, the concentration of HF should not be too high, otherwise it will destroy the shape of the material and make it incomplete.

[0039] Step 3: The Cu-SAC obtained in step 2 was dispersed in a solution containing glucose oxidase GOx, stirred at a speed of 200 r / min in the dark, stirred for 12 h, centrifuged and washed to remove excess GOx, and freeze-dried to obtain Cu-SAC@GOx, where the mass ratio of Cu-SAC to GOx was 1:2.

[0040] GOx is a macromolecular protein containing flavin adenine dinucleotide (FAD) cofactor, which can catalyze the oxidation of glucose to produce gluconic acid and H2O2. High temperature and light will cause it to lose its enzyme activity, so low-temperature freeze-drying and light-proof stirring can prevent thermal decomposition and photooxidation to maintain enzyme activity.

[0041] Step 4: The Cu-SAC@GOx obtained in step 3 was placed in a hyaluronic acid HA solution, stirred at a speed of 200 r / min, stirred for 1 h, and the mixture was centrifuged at 9000 r / min for 15 min, freeze-dried to obtain HA@Cu-SAC@GOx, and stored at 4 °C for further experiments. Due to the high-temperature carbonization, a large number of oxygen vacancies were generated on the surface of Cu-SAC, and HA could be adsorbed on the surface of Cu-SAC.

[0042] Example 1 A method for preparing a high-load copper single-atom nanozyme comprises the following steps: Step 1: Add SiO2 particles to a mixed solution of resorcinol and formaldehyde, and after sufficient reaction and mixing, add a solution containing copper ions, and after sufficient reaction, wash, centrifuge, and dry to obtain a precursor material SiO2 / Cu-HCN.

[0043] First prepare SiO2: Mix 10 mL of ammonia water, 160 mL of ethanol, and 20 mL of RO water and divide it into three portions of 190 mL, 10 mL, and 10 mL as solvents A, B, and C. Add solvent A into a three-necked flask, set the speed to 400 r / min, take 10 mL of 0.1 mol / L tetrapropoxysilane solution and 10 mL of 0.1 mol / L ethyl orthosilicate solution and add them into the dropping funnel respectively, and add them dropwise to solution A. Control the dropping speed to 0.5 mL / min. After the addition is completed, increase the speed to 500 r / min and react for 2 h to obtain solution D.

[0044] After 2 h, 1.9 mmol of resorcinol powder was dissolved in solvent B and ultrasonically vibrated until completely dissolved. Then 2 mL of 37% formaldehyde solution was dissolved in solvent C. The two were added to the dropping funnel and dripped. The dripping speed was controlled to 0.5 mL / min. The rotation speed in solution D was adjusted to 400 r / min. After the dripping was completed, the rotation speed was adjusted to 900 r / min to obtain solution E. After continuing the reaction for 10 h, 200 μL of copper chloride solution was added, in which the copper chloride content was 0.1 mM. The original rotation speed was kept unchanged for 12 h. In order to maintain a constant temperature, the reaction device was placed in the water area, and the water in the water area was continuously replaced to maintain it at room temperature. After the reaction was completed, the reaction solution was washed twice with 95% ethanol and RO water to remove ammonia and ethanol, and then centrifuged at 9000 r / min for 15 min. Finally, SiO2 / Cu-HCN was obtained after drying at 60 °C for 6 h.

[0045] Step 2: Grind the SiO2 / Cu-HCN obtained in step 1 thoroughly, take 3 g and mix it with 9 g urea; place it in a quartz crucible and transfer it to a tube furnace, and heat it in an argon atmosphere for carbonization; before heating, pass argon for 10 minutes to remove oxygen, then heat it to 900 °C at a heating rate of 4 °C / min, keep it for 2 hours, then cool it naturally to room temperature and take it out, add all the products to 10% HF solution to obtain solution F, and stir it for 12 hours. After stirring, wash it with 95% ethanol and RO water until it is neutral, then centrifuge it at 9000 r / min for 15 minutes, and finally dry it at 60 °C for 6 hours to obtain Cu-SAC.

[0046] Step 3: Disperse 2 g of the Cu-SAC obtained in step 2 in a solution containing 4 g of glucose oxidase GOx, stir the reaction at a stirring speed of 200 r / min in the dark for 12 h, centrifuge and wash with RO water to remove excess GOx, then centrifuge at 9000 r / min for 15 min and dry with a freeze dryer to obtain Cu-SAC@GOx.

[0047] Step 4: Take 2 g of the Cu-SAC@GOx obtained in step 3 and place it in a solution containing 4 g of hyaluronic acid HA. Stir the reaction at a stirring speed of 200 r / min for 1 h. Centrifuge at 9000 r / min for 15 min, freeze-dry to obtain HA@Cu-SAC@GOx, and store it at 4 °C for further experiments.

[0048] Example 2 A method for preparing a high-load copper single-atom nanozyme comprises the following steps: Step 1: Add SiO2 particles to a mixed solution of resorcinol and formaldehyde, and after sufficient reaction and mixing, add a solution containing copper ions, and after sufficient reaction, wash, centrifuge, and dry to obtain a precursor material SiO2 / Cu-HCN.

[0049] First prepare SiO2: Mix 12 mL of ammonia water, 160 mL of ethanol, and 40 mL of RO water and divide it into three portions of 172 mL, 20 mL, and 20 mL as solvents A, B, and C. Add solvent A into a three-necked flask, set the speed to 400 r / min, take 20 mL of 0.05 mol / L tetrapropoxysilane solution and 20 mL of 0.07 mol / L ethyl orthosilicate solution and add them into the dropping funnel respectively, and add them dropwise to solution A. Control the dropping speed to 0.5 mL / min. After the addition is completed, increase the speed to 600 r / min and react for 2 h to obtain solution D.

[0050] After 2 h, 2.25 mmol of resorcinol powder was dissolved in solvent B and ultrasonically vibrated until completely dissolved. Then 5 mL of 37% formaldehyde solution was dissolved in solvent C. The two were added to the dropping funnel and dripped. The dripping speed was controlled to 0.5 mL / min. The rotation speed in solution D was adjusted to 400 r / min. After the dripping was completed, the rotation speed was adjusted to 1000 r / min to obtain solution E. After continuing the reaction for 10 h, 200 μL of copper chloride solution was added, in which the copper chloride content was 0.3 mM. The original rotation speed was kept unchanged for 12 h. In order to maintain a constant temperature, the reaction device was placed in the water area, and the water in the water area was continuously replaced to maintain it at room temperature. After the reaction was completed, the reaction solution was washed twice with 95% ethanol and RO water to remove ammonia and ethanol, and then centrifuged at 9000 r / min for 15 min. Finally, SiO2 / Cu-HCN was obtained after drying at 60 °C for 6 h.

[0051] Step 2: Grind the SiO2 / Cu-HCN obtained in step 1 thoroughly, take 2 g and mix it with 8 g urea; place it in a quartz crucible and transfer it to a tube furnace, and heat it in an argon atmosphere for carbonization; before heating, pass argon for 10 minutes to remove oxygen, then heat it to 900 °C at a heating rate of 4 °C / min, keep it for 2 hours, then cool it naturally to room temperature and take it out, add all the products to 10% HF solution to obtain solution F, and stir it for 12 hours. After stirring, wash it with 95% ethanol and RO water until it is neutral, then centrifuge it at 9000 r / min for 15 minutes, and finally dry it at 60 °C for 6 hours to obtain Cu-SAC.

[0052] Step 3: Disperse 2 g of the Cu-SAC obtained in step 2 in a solution containing 4 g of glucose oxidase GOx, stir the reaction at a stirring speed of 200 r / min in the dark for 12 h, centrifuge and wash with RO water to remove excess GOx, then centrifuge at 9000 r / min for 15 min and dry with a freeze dryer to obtain Cu-SAC@GOx.

[0053] Step 4: Take 2 g of the Cu-SAC@GOx obtained in step 3 and place it in a solution containing 4 g of hyaluronic acid HA. Stir the reaction at a stirring speed of 200 r / min for 1 h. Centrifuge at 9000 r / min for 15 min, freeze-dry to obtain HA@Cu-SAC@GOx, and store it at 4 °C for further experiments.

[0054] Example 3 A method for preparing a high-load copper single-atom nanozyme comprises the following steps: Step 1: Add SiO2 particles to a mixed solution of resorcinol and formaldehyde, and after sufficient reaction and mixing, add a solution containing copper ions, and after sufficient reaction, wash, centrifuge, and dry to obtain a precursor material SiO2 / Cu-HCN.

[0055] First prepare SiO2: Mix 20 mL of ammonia water, 240 mL of ethanol, and 60 mL of RO water and divide it into three portions of 260 mL, 30 mL, and 30 mL as solvents A, B, and C. Add solvent A into a three-necked flask, set the speed to 400 r / min, take 20 mL of 0.1 mol / L tetrapropoxysilane solution and 32 mL of 0.1 mol / L ethyl orthosilicate solution and add them into the dropping funnel respectively. Add dropwise to solution A, control the dropping speed to 0.5 mL / min, increase the speed to 600 r / min after the addition is completed, react for 2 h, and obtain solution D.

[0056] After 2 h, 2.6 mmol of resorcinol powder was dissolved in solvent B and ultrasonically vibrated until completely dissolved. Then 2 mL of 37% formaldehyde solution was dissolved in solvent C. The two were added to the dropping funnel and dripped. The dripping speed was controlled to 0.5 mL / min. The rotation speed in solution D was adjusted to 400 r / min. After the dripping was completed, the rotation speed was adjusted to 1000 r / min to obtain solution E. After continuing the reaction for 10 h, 500 μL of copper chloride solution was added, in which the copper chloride content was 0.4 mM. The original rotation speed was kept unchanged for 12 h. In order to maintain a constant temperature, the reaction device was placed in the water area, and the water in the water area was continuously replaced to maintain it at room temperature. After the reaction was completed, the reaction solution was washed twice with 95% ethanol and RO water to remove ammonia and ethanol, and then centrifuged at 9000 r / min for 15 min. Finally, SiO2 / Cu-HCN was obtained after drying at 60 °C for 6 h.

[0057] Step 2: Grind the SiO2 / Cu-HCN obtained in step 1 thoroughly, take 5 g and mix it with 15 g urea; place it in a quartz crucible and transfer it to a tube furnace, and heat it in an argon atmosphere for carbonization; before heating, pass argon for 10 minutes to remove oxygen, then heat it to 900 °C at a heating rate of 4 °C / min, keep it for 2 hours, then cool it naturally to room temperature and take it out, add all the products to 10% HF solution to obtain solution F, and stir it for 12 hours. After stirring, wash it with 95% ethanol and RO water until it is neutral, then centrifuge it at 9000 r / min for 15 minutes, and finally dry it at 60 °C for 6 hours to obtain Cu-SAC.

[0058] Step 3: 4 g of Cu-SAC obtained in step 2 was dispersed in a solution containing 8 g of glucose oxidase GOx, and the mixture was stirred at 200 r / min in the dark for 12 h. After centrifugation, the mixture was washed with RO water to remove excess GOx, and then centrifuged at 9000 r / min for 15 min and dried using a freeze dryer to obtain Cu-SAC@GOx.

[0059] Step 4: Take 3 g of the Cu-SAC@GOx obtained in step 3 and place it in a solution containing 6 g of hyaluronic acid HA. Stir the reaction at a stirring speed of 200 r / min for 1 h. Centrifuge at 9000 r / min for 15 min, freeze-dry to obtain HA@Cu-SAC@GOx, and store it at 4 °C for further experiments.

[0060] Example 4 A method for preparing a high-load copper single-atom nanozyme comprises the following steps: Step 1: Add SiO2 particles to a mixed solution of resorcinol and formaldehyde, and after sufficient reaction and mixing, add a solution containing copper ions, and after sufficient reaction, wash, centrifuge, and dry to obtain a precursor material SiO2 / Cu-HCN.

[0061] First prepare SiO2: Mix 20 mL of ammonia water, 240 mL of ethanol, and 60 mL of RO water and divide it into three portions of 260 mL, 30 mL, and 30 mL as solvents A, B, and C. Add solvent A into a three-necked flask, set the speed to 400 r / min, take 25 mL of 0.1 mol / L tetrapropoxysilane solution and 45 mL of 0.1 mol / L ethyl orthosilicate solution and add them into the dropping funnel respectively. Add dropwise to solution A, control the dropping speed to 0.5 mL / min, increase the speed to 600 r / min after the addition is completed, react for 2 h, and obtain solution D.

[0062] After 2 h, 3.2 mmol of resorcinol powder was dissolved in solvent B and ultrasonically vibrated until completely dissolved. Then 8 mL of 37% formaldehyde solution was dissolved in solvent C. The two were added to the dropping funnel and dripped. The dripping speed was controlled to 0.5 mL / min. The rotation speed in solution D was adjusted to 400 r / min. After the dripping was completed, the rotation speed was adjusted to 1000 r / min to obtain solution E. After continuing the reaction for 10 h, 500 μL of copper chloride solution was added, in which the copper chloride content was 0.5 mM. The original rotation speed was kept unchanged for 12 h. In order to maintain a constant temperature, the reaction device was placed in the water area, and the water in the water area was continuously changed to maintain it at room temperature. After the reaction was completed, the reaction solution was washed twice with 95% ethanol and RO water to remove ammonia and ethanol, and then centrifuged at 9000 r / min for 15 min. Finally, SiO2 / Cu-HCN was obtained after drying at 60 °C for 6 h.

[0063] Step 2: Grind the SiO2 / Cu-HCN obtained in step 1 thoroughly, take 5 g and mix it with 20 g urea; place it in a quartz crucible and transfer it to a tube furnace, and heat it in an argon atmosphere for carbonization; before heating, pass argon for 10 minutes to remove oxygen, then heat it to 900 °C at a heating rate of 4 °C / min, keep it for 2 hours, then cool it naturally to room temperature and take it out, add all the products to 10% HF solution to obtain solution F, and stir it for 12 hours. After stirring, wash it with 95% ethanol and RO water until it is neutral, then centrifuge it at 9000 r / min for 15 minutes, and finally dry it at 60 °C for 6 hours to obtain Cu-SAC.

[0064] Step 3: 4 g of Cu-SAC obtained in step 2 was dispersed in a solution containing 8 g of glucose oxidase GOx, and the mixture was stirred at 200 r / min in the dark for 12 h. After centrifugation, the mixture was washed with RO water to remove excess GOx, and then centrifuged at 9000 r / min for 15 min and dried using a freeze dryer to obtain Cu-SAC@GOx.

[0065] Step 4: Take 3 g of the Cu-SAC@GOx obtained in step 3 and place it in a solution containing 6 g of hyaluronic acid HA. Stir the reaction at a stirring speed of 200 r / min for 1 h. Centrifuge at 9000 r / min for 15 min, freeze-dry to obtain HA@Cu-SAC@GOx, and store it at 4 °C for further experiments.

[0066] Example 5 A method for preparing a high-load copper single-atom nanozyme comprises the following steps: Step 1: Add SiO2 particles to a mixed solution of resorcinol and formaldehyde, and after sufficient reaction and mixing, add a solution containing copper ions, and after sufficient reaction, wash, centrifuge, and dry to obtain a precursor material SiO2 / Cu-HCN.

[0067] First prepare SiO2: Mix 30 mL of ammonia water, 240 mL of ethanol, and 60 mL of RO water and divide it into three portions of 260 mL, 35 mL, and 35 mL as solvents A, B, and C. Add solvent A into a three-necked flask, set the speed to 400 r / min, take 25 mL of 0.1 mol / L tetrapropoxysilane solution and 25 mL of 0.2 mol / L ethyl orthosilicate solution and add them into the dropping funnel respectively, add them dropwise to solution A, control the dropping speed to 0.5 mL / min, increase the speed to 600 r / min after the addition is completed, react for 2 h, and obtain solution D.

[0068] After 2 h, 5 mmol of resorcinol powder was dissolved in solvent B and ultrasonically vibrated until completely dissolved. Then 8 mL of 37% formaldehyde solution was dissolved in solvent C. The two were added to the dropping funnel and dripped. The dripping speed was controlled to 0.5 mL / min. The rotation speed in solution D was adjusted to 400 r / min. After the dripping was completed, the rotation speed was adjusted to 1000 r / min to obtain solution E. After continuing the reaction for 10 h, 500 μL of copper chloride solution was added, in which the copper chloride content was 0.5 mM. The original rotation speed was kept unchanged for 12 h. In order to maintain a constant temperature, the reaction device was placed in the water area, and the water in the water area was continuously replaced to maintain it at room temperature. After the reaction was completed, the reaction solution was washed twice with 95% ethanol and RO water to remove ammonia and ethanol, and then centrifuged at 9000r / min for 15 min. Finally, SiO2 / Cu-HCN was obtained after drying at 60 °C for 6 h.

[0069] Step 2: Grind the SiO2 / Cu-HCN obtained in step 1 thoroughly, take 5 g and mix it with 20 g urea; place it in a quartz crucible and transfer it to a tube furnace, and heat it in an argon atmosphere for carbonization; before heating, pass argon for 10 minutes to remove oxygen, then heat it to 900 °C at a heating rate of 4 °C / min, keep it for 2 hours, then cool it naturally to room temperature and take it out, add all the products to 10% HF solution to obtain solution F, and stir it for 12 hours. After stirring, wash it with 95% ethanol and RO water until it is neutral, then centrifuge it at 9000 r / min for 15 minutes, and finally dry it at 60 °C for 6 hours to obtain Cu-SAC.

[0070] Step 3: Disperse 3 g of the Cu-SAC obtained in step 2 in a solution containing 6 g of glucose oxidase GOx, stir the solution at a stirring speed of 200 r / min in the dark for 12 h, centrifuge and wash with RO water to remove excess GOx, then centrifuge at 9000 r / min for 15 min and dry with a freeze dryer to obtain Cu-SAC@GOx.

[0071] Step 4: Take 4 g of Cu-SAC@GOx obtained in step 3 and place it in a solution containing 8 g of hyaluronic acid HA. Stir the reaction at a stirring speed of 200 r / min for 1 h. Centrifuge at 9000 r / min for 15 min, freeze-dry to obtain HA@Cu-SAC@GOx, and store it at 4 °C for further experiments.

[0072] Comparative Example 1 In order to illustrate the beneficial effects of the present invention, a comparative example is set, with the carbonized SiO2 / HCN (CS) material as a comparison, and the specific preparation method is as follows: Step 1: Mix 10 mL of ammonia water, 160 mL of ethanol, and 20 mL of RO water, and divide it into three portions of 190 mL, 10 mL, and 10 mL as solvents A, B, and C. Add solvent A into a three-necked flask, set the speed to 400 r / min, take 10 mL of 0.1 mol / L tetrapropoxysilane solution and 10 mL of 0.1 mol / L ethyl orthosilicate solution and add them into the dropping funnel respectively, and add them dropwise into solution A. Control the dropping speed to 0.5 mL / min. After the addition is completed, increase the speed to 500 r / min and react for 2 h to obtain solution D.

[0073] After 2 h, 1.9 mmol of resorcinol powder was dissolved in solvent B and ultrasonically vibrated until completely dissolved. Then 2 mL of 37% formaldehyde solution was dissolved in solvent C. The two were added to the dropping funnel and dripped. The dripping speed was controlled to 0.5 mL / min. The rotation speed in solution D was adjusted to 400 r / min. After the dripping was completed, the rotation speed was adjusted to 900 r / min to obtain solution E. The reaction was continued for 22 h. In order to maintain a constant temperature, the reaction device was placed in the water area, and the water in the water area was continuously replaced to maintain it at room temperature. After the reaction was completed, the reaction solution was washed twice with 95% ethanol and RO water to remove ammonia and ethanol, and then centrifuged at 9000 r / min for 15 min. Finally, SiO2 / HCN was obtained after drying at 60 °C for 6 h.

[0074] Step 2: After fully grinding the SiO2 / HCN obtained in step 1, take 3 g and mix it with 9 g urea and put it into a quartz crucible, and transfer it to a tube furnace for high-temperature carbonization. Before heating, pass argon for 10 minutes to remove oxygen, then heat it to 900 °C at a heating rate of 4 °C / min, keep it for 2 hours, then cool it naturally to room temperature and take it out, add all the products together to 10% HF solution to obtain solution F, and stir it for 12 hours. After stirring, wash it with 95% ethanol and RO water until it is neutral, then centrifuge it at 9000 r / min for 15 minutes, and finally dry it at 60 °C for 6 hours to obtain CS.

[0075] Figure 2The schematic diagram of the microstructure of Cu-SAC obtained in step 2 of Example 1 of the present invention, a is a SEM image, b is a TEM image, and c is an AC-HAADF-STEM image. It can be seen from a and b that the Cu-SAC obtained in step 2 is a uniformly dispersed hollow spherical particle with an average particle size of about 110 nm, indicating that the catalyst is suitable for a nano drug delivery system. c is a spherical aberration-high angle annular dark field scanning transmission electron microscope (AC-HAADF-STEM) of Cu-SAC. A large number of clear bright dots (highlighted by circles) can be observed in the image. This is atomically dispersed copper. No clusters or nanoscale particles are observed, proving that copper is uniform and dispersed on the carrier at the atomic level.

[0076] Figure 3 Schematic diagram of the test results of Cu-SAC obtained in step 2 of Example 1 of the present invention, a is the specific surface area and pore size distribution, b is the X-ray diffraction diagram, and c is the Raman spectrum of the substances obtained in comparative example 1 and step 2. Figure 3 a is the nitrogen adsorption-desorption isotherm of Cu-SAC. It can be seen from the figure that Cu-SAC has a hysteresis loop of type IV isotherm and a specific surface area of ​​265.2 m 2 g −1 , the average pore size calculated based on the BJH method is 6.9 nm. From b, it can be seen that the two broad diffraction peaks of the (002) and (100) crystal planes belong to graphite carbon, and no copper crystallization peak appears. c is the Raman spectrum of the material obtained in comparative example 1 and step 2. Graphitized carbon has two typical peaks in the Raman spectrum, at about 1390 cm -1 The D peak at 1530 cm -1 The G peak nearby is also related to defects, indicating the degree of order in the material structure. The half-width of the G peak is positively correlated with the degree of defects. ID / IG describes the degree of graphitization of the sample. The ID / IG values ​​of Cu-SAC and CS are 1.23 and 1.11, respectively, which indicates that due to the introduction of N and Cu into the carbon skeleton in Cu-SAC, the defects of Cu-SAC are significantly increased compared with carbon spheres.

[0077] Figure 4 Schematic diagram of the test results of Cu-SAC obtained in step 2 of Example 1 of the present invention, a is the normalized XANES spectrum of Cu K edge with copper foil, Cu2O and CuO, b is the FT-EXAFS spectrum with copper foil, Cu2O and CuO, c is the EXAFS fitting result in R space, and d is the EXAFS fitting result in K space. Figure 4From a, we can see that the energy absorption threshold of Cu in Cu-SAC is between copper foil and copper oxide, which verifies the oxidation state of Cu (Cuδ+, 0<δ<2) in Cu-SAC. From b and c, we can see that Cu-SAC has a main peak at about 1.47Å, which is attributed to the Cu-N path in the first shell. The difference in values ​​from copper-foil (2.35Å) and copper-oxygen (1.53Å) is because the different atomic numbers of nitrogen, oxygen, and copper lead to different electron layers of neighboring atoms, so the interference between the ionized photoelectron waves and the backscattered waves of some of these waves by neighboring atoms will also change. d is the k-space data image obtained by fitting the Cu k-edge data of Cu-SAC using phthalocyanine as a standard reference using Artemis software and comparing it with copper-foil, Cu2O and CuO. The results show that the local atomic environment of Cu is a weighted average. Due to the disordered nature and edge defects, the EXAFS data of Cu-SAC shows more noise compared with other samples. Therefore, in Cu-SAC, the Cu-N structure most likely exists in the form of Cu-N4.

[0078] Figure 5 The test results of the substances obtained in each step of Example 1 of the present invention are shown in Figure 1. a is a comparison of the ultraviolet absorption spectra of the reaction of H2O2 and GOx with TMB of the materials obtained in step 2, step 3 and Example 1. b is the electron spin resonance spectrum of the material obtained in Example 1 in the presence or absence of H2O2. The 3,3',5,5'-tetramethylbenzidine (TMB) method was used to investigate the oxidation of TMB by H2O2, GOx, the substances obtained in steps 2 and 3 and Example 1 in the presence of H2O2. TMB can be oxidized by ∙OH to produce a blue-green complex precipitate (oxTMB), with characteristic ultraviolet peaks at 370 nm and 650 nm. H2O2 and GOx alone do not produce ROS, so the UV spectrum tends to be linear; Cu-SAC can adsorb H2O2 and efficiently produce ·OH at single-atom sites, so oxTMB is detected with a clear peak; Cu-SAC@GOx and HA@Cu-SAC@GOx can catalyze glucose to produce more H2O2, so increasing the concentration of Fenton-like reactants can effectively improve the catalytic efficiency and induce the generation of more ·OH. Figure 5 As can be seen in b, electron spin resonance (ESR) spectroscopy also shows a typical ·OH quadruple signal (1:2:2:1), indicating that ·OH has excellent biocatalytic properties, which is consistent with the TMB determination results.

[0079] Figure 6The biocompatibility results of the substances obtained in each step of Example 1 of the present invention, a is the EC cell result, b is the MCF cell result, and c is the 4T1 cell result. Different concentrations of Cu-SAC obtained in step 2, Cu-SAC@GOx obtained in step 3, and HA@Cu-SAC@GOx obtained in Example 1 were incubated with human breast cancer cells (MCF-7) and mouse breast cancer cells (4T1) respectively to investigate their toxicity to the cells. The MTT method was used to test the toxicity to the cells (the MTT method is a commonly used cytotoxicity detection method that can detect the toxicity of nanocatalysts to tumor cells. The principle is that succinate dehydrogenase (SDH) in living cells can reduce MTT to water-insoluble blue-purple crystals, but has no effect on dead cells. The absorbance value of the blue-purple crystals at a wavelength of 490 nm was measured by an ELISA instrument. Within a certain range, the amount of MTT purple crystals is proportional to the number of living cells. The stronger the absorbance value, the more living cells there are). The results are as follows Figure 6 As shown in b and c, compared with the Cu-SAC group alone, the cell killing effects of Cu-SAC@GOx and HA@Cu-SAC@GOx were greatly improved, and the survival rate of MCF-7 and 4T1 cells treated with HA@Cu-SAC@GOx was less than 20%, indicating that under the targeted effect, the efficacy of CDT was enhanced while achieving efficient synergistic killing of tumor cells by starvation therapy and CDT.

[0080] Figure 7 The fluorescence images of ROS generation in 4T1 cells obtained in each step of Example 1 of the present invention are shown in Figure 1. The fluorescence images of ROS generation in 4T1 cells were investigated using the DCFH-DA probe. In order to confirm that the single-atom catalyst mediates the effective generation and accumulation of ROS in tumor cells, we used the intracellular ROS probe 2,7-dichlorofluorescein diacetate (DCFH-DA) to stain the cells. The results are shown in Figure 1. Figure 7 As shown. The cell fluorescence of the Cu-SAC group is low because the Cu-SAC single-atom catalyst generates ROS only by CDT treatment alone, and the elimination of GSH and endogenous H2O2 concentration in the cell are insufficient, resulting in limited ROS generation. The fluorescence intensity of the Cu-SAC@GOx group is improved because the loading of GOx can provide exogenous H2O2 to promote the generation of ROS. The cells in the HA@Cu-SAC@GOx group show the highest fluorescence, and under the dual blessing of GOx and targeting, a large amount of ROS is induced to be efficiently generated.

[0081] Figure 8 The fluorescence image of ·OH in 4T1 cells obtained in each step of Example 1 of the present invention is shown in Figure 1. The fluorescence image of ·OH in 4T1 cells detected by APF probe is shown in Figure 1. Figure 8As shown in Figure 2, consistent with the rule of DCFH-DA probe, HA@Cu-SAC@GOx produced the highest ·OH level and the strongest fluorescence intensity.

[0082] Fig. 9 The CLSM images of the mitochondrial membrane potential of 4T1 cells obtained in each step of Example 1 of the present invention are shown in Figure 1. In order to evaluate whether mitochondrial function is impaired after different treatments, a mitochondrial membrane potential detection kit (JC-1) was used to detect mitochondrial damage. JC-1 with normal membrane potential presents red aggregates. When the mitochondria are damaged, the potential decreases and JC-1 presents monomers with depolarized membranes. The results are consistent with the above results of intracellular ROS levels ( Figure 7 ). The fluorescence intensity ratio of the two colors of the Cu-SAC and Cu-SAC@GOx groups increased, and the fluorescence intensity of the HA@Cu-SAC@GOx group was further enhanced. The oxidative damage mediated by the final product multifunctional single-atom catalyst group caused severe mitochondrial dysfunction.

[0083] Fig.10 The cytotoxicity test results of the materials obtained in each step of Example 1 of the present invention, a is the fluorescent staining image using AM / PI probe to detect material toxicity, and b is the apoptosis rate caused by incubation of 4T1 cells with different materials measured by flow cytometry. The cell survival was observed by staining with calcein (Calcein-AM) and propidium iodide (PI), and the killing ability of single-atom catalysts on tumor cells was investigated. The results showed that the damage to 4T1 cells treated with Cu-SAC alone was negligible, Cu-SAC induced the death of some cancer cells, and HA@Cu-SAC@GOx had the strongest killing effect on tumor cells, which was consistent with the results of the MTT method. The cells were analyzed for apoptosis using the Annexin V-FITC and PI double staining kit, and the results are shown in the figure. Fig.10 As shown in a. Fig.10 In b, it can be seen that there is no obvious apoptosis in the control group. In the Cu-SAC group, the percentages of early apoptotic cells and late apoptotic cells were 17.63% and 22.09%, respectively; the early apoptotic cells and late apoptotic cells of Cu-SAC@GOx increased to 17.49% and 38.92%, indicating that the CDT efficacy was slightly enhanced under the action of exogenous H2O2; in the HA@Cu-SAC@GOx group, the percentages of early apoptotic cells and late apoptotic / dead cells were the highest, reaching 23.89% and 61.73%, respectively. The apoptosis rate results are completely consistent with the cytotoxicity experimental investigation.

[0084] The present invention uses hollow mesoporous carbon spheres as a matrix, anchors Cu through the surface N site, and successfully synthesizes copper single-atom carbon spheres Cu-SAC. The hollow structure is used to load glucose oxidase GOx, which provides H2O2 as an exogenous oxidoreductase to solve the problem of insufficient H2O2 content in the tumor microenvironment, and at the same time plays the role of starvation therapy to block the energy supply of the tumor site. The Fenton-like reaction with the high concentration of H2O2 in the tumor site accumulates highly oxidizing OH with the ability to damage cells, depletes GSH while reducing its elimination effect on ROS, thereby killing cancer cells. The present invention uses copper-doped precursor products to prepare copper single-atom hollow mesoporous carbon spheres, loads GOx and performs HA modification to obtain nanozymes, which provides a new construction idea for the design and biomedical application of new nanocatalysts.

Claims

1. A method for preparing a high-load copper single-atom nanozyme, characterized in that: The following steps are involved: Step 1: Add SiO2 particles to a mixed solution of resorcinol and formaldehyde, fully react and mix, then add a solution containing copper ions, fully react, wash, centrifuge, and dry to obtain a precursor material SiO2 / Cu-HCN; Step 2: Fully mix the SiO2 / Cu-HCN obtained in step 1 with a nitrogen source, and obtain a carbon precursor material after carbonization; remove the remaining SiO2 to obtain Cu-SAC; Step 3: Disperse the Cu-SAC obtained in step 2 in a solution containing glucose oxidase GOx, fully react, wash, centrifuge, and freeze-dry to obtain Cu-SAC@GOx; Step 4: Place the Cu-SAC@GOx obtained in step 3 in a hyaluronic acid HA solution, allow to react fully, and then centrifuge and freeze-dry to obtain the desired high-load copper single-atom nanozyme HA@Cu-SAC@GOx.

2. The method for preparing a high-load copper single-atom nanozyme according to claim 1, characterized in that: The SiO2 preparation method in step 1 is as follows: Tetrapropoxysilane and ethyl orthosilicate are dispersed in an alkaline solvent at a molar ratio of 1:1-2 and reacted under stirring conditions.

3. The method for preparing a high-load copper single-atom nanozyme according to claim 2, characterized in that: In the step 1, the molar ratio of tetrapropoxysilane to resorcinol is 1:1.25-2, the concentration of copper ions in the copper ion-containing solution is 0.1-1 mM, and the reaction is carried out under stirring conditions.

4. The method for preparing a high-load copper single-atom nanozyme according to claim 1, characterized in that: In step 2, the nitrogen source is urea, and the mass ratio of SiO2 / Cu-HCN to urea is 1:3-4.

5. The method for preparing a high-load copper single-atom nanozyme according to claim 1, characterized in that: In step 2, the carbonization temperature is 900°C, the heating rate is 4°C / min, and the heating time is 2 h.

6. The method for preparing a high-load copper single-atom nanozyme according to claim 1, characterized in that: In step 2, HF solution is used to remove the remaining SiO2, and the concentration of the HF solution is 10 wt.%.

7. The method for preparing a high-load copper single-atom nanozyme according to claim 1, characterized in that: In step 3, the mass ratio of Cu-SAC to GOx is 1:2, and the reaction is carried out under stirring.

8. The method for preparing a high-load copper single-atom nanozyme according to claim 1, characterized in that: In step 4, the mass ratio of Cu-SAC@GOx to HA is 1:2, and the reaction is carried out under stirring conditions.

9. The high-load copper single-atom nanozyme obtained by the preparation method according to any one of claims 1 to 8, characterized in that: The nanozyme is a mesoporous hollow structure on which single copper atoms are loaded.

10. The use of a high-load copper single-atom nanozyme as claimed in claim 9, characterized in that: The application of the nanozyme in the preparation of tumor treatment drugs.

Citation Information

Patent Citations

  • Nitrogen-doped hollow mesoporous carbon sphere loaded nano platinum electrocatalytic hydrogen evolution material for cathode of PEM electrolytic cell, preparation and application of nitrogen-doped hollow mesoporous carbon sphere loaded nano platinum electrocatalytic hydrogen evolution material

    CN115852388A

  • Preparation and application of hollow carbon drug delivery system with enzyme-like activity

    CN116966296A

  • Mesoporous hollow copper monatomic carbon sphere, preparation method and application

    CN117045823A

  • Sea-urchin-shaped carbon nanoparticle-loaded copper monatomic nano-enzyme as well as preparation method and application thereof

    CN118491519A

  • Preparation method of cascade catalytic nano reaction system

    CN118976107A